1999
DOI: 10.1016/s0893-133x(99)00044-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies and Antisense Oligonucleotide for Probing the Distribution and Putative Functions of Central 5-HT6 Receptors

Abstract: Among the recently cloned serotonin (5-hydroxytryptamine, 5-HT) receptors, the 5-HT6 subtype is of special interest for at least two reasons: 1) it is abundant in limbic areas which participate in the control of mood and emotion; and 2) some antidepressants and antipsychotics are potent 5-HT6 receptor antagonists. Studies using polyclonal anti-5-HT6 receptor antibodies and an antisense oligonucleotide were performed in order to investigate further the function(s) of 5-HT6 receptors in the rat brain. Immunocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 31 publications
(36 reference statements)
5
100
0
1
Order By: Relevance
“…In rats, continuous intraventricular infusion of 5-HT 6 R antisense oligonucleotides evoked increased anxiety-related behaviors on an elevated plus maze and a social interaction test (Hamon et al, 1999;Otano et al, 1999). However, similar treatments failed to alter conditioned freezing responses in rats (Yoshioka et al, 1998).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 95%
See 2 more Smart Citations
“…In rats, continuous intraventricular infusion of 5-HT 6 R antisense oligonucleotides evoked increased anxiety-related behaviors on an elevated plus maze and a social interaction test (Hamon et al, 1999;Otano et al, 1999). However, similar treatments failed to alter conditioned freezing responses in rats (Yoshioka et al, 1998).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 95%
“…Thus, the expression pattern and pharmacological properties of Rs indicate that they may contribute to serotonergic modulation of clinically relevant neuropsychological processes and psychopharmacological responses. Administration of 5-HT 6 R antagonists and antisense oligonucleotides have been reported to produce several behavioral effects in rodents, including feeding suppression (Svartengren et al, 2004), yawning and stretching (Bourson et al, 1995;Sleight et al, 1996;Sleight et al, 1998;Bentley et al, 1999), decreased anxiety-related behaviors (Hamon et al, 1999), and improved performance in learning and memory tasks (Meneses, 2001;Rogers and Hagan, 2001;Woolley et al, 2001;Russell and Dias, 2002;Lindner et al, 2003;Riemer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in situ hybridization studies have shown robust mRNA expression in rat and human striatum, nucleus accumbens, cortex and olfactory tubercle, with moderate expression in the hippocampus and thalamus (Gerard et al, 1996;Ward and Dorsa, 1996), whereas expression in mouse brain is very low compared to rat or human brain (Hirst et al, 2003). Immunohistochemical localization of 5-HT 6 receptors has been detected in the above regions as well as the cerebellum and substantia nigra (Gerard et al, 1997;Hamon et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…As the regional distribution of 5-HT 6 receptor generally matched that found for the 5-HT 6 receptor mRNA, it is likely that the former is mainly localized on somas and/or dendrites of neurons. This conclusion is further supported by light and electron microscopy immunoreactivity data clearly showing the localization of this receptor on dendritic processes of spiny neurons in the striatum (Gerard et al, 1997;Hamon et al, 1999). Finally, selective lesion of 5-HT neurons by injection of 5,7-dihydroxytryptamine (5,7-DHT) in the DRN has been shown to not affect the levels of 5-HT 6 mRNA in the striatum of rat brain, thus confirming the postsynaptic localization of this receptor with respect to 5-HT neurons innervating this area (Gerard et al, 1996).…”
Section: Striatummentioning
confidence: 52%